K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 12 2018

mở sách giải ra mà cop

1 tháng 12 2018

\(C=\frac{1}{x^2+6x+9}+\frac{1}{6x-x^2-9}+\frac{x}{x^2-9}.\)

\(C=\frac{1}{\left(x+3\right)^2}+\frac{-1}{-\left(6x-x^2-9\right)}+\frac{x}{\left(x+3\right)\left(x-3\right)}\)

\(C=\frac{1}{\left(x+3\right)^2}+\frac{-1}{-6x+x^2+9}+\frac{x}{\left(x+3\right)\left(x-3\right)}\)

\(C=\frac{x-3}{\left(x+3\right)\left(x-3\right)}+\frac{-\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}+\frac{x}{\left(x+3\right)\left(x-3\right)}\)

\(C=\frac{x-3.-x-3.x}{\left(x+3\right).\left(x-3\right)}=\frac{-6x}{\left(x+3\right)\left(x-3\right)}=\frac{-6x}{\left(x^2-9\right)}\)

1 tháng 12 2018

\(x^4-2x^2+1+x^2+2x+1+2018=\left(x^2-1\right)^2+\left(x+1\right)^2+2018\ge2018\)

Dấu "=" xayr ra <=> \(\hept{\begin{cases}x^2-1=0\\x+1=0\end{cases}\Leftrightarrow x=-1}\)

Kết luận :...